Moisturisers in scar management following burn: A survey report. Issue 5 (August 2017) - Klotz, Tanja; Kurmis, Rochelle; Munn, Zachary; Heath, Kathryn; Greenwood, John
Highlights: Out of 53 therapists there are 29 different moisturisers recommended. Sources of knowledge was mostly patient feedback or the previous therapist. 3 respondents were able to provide evidence for their recommendations. There is a paucity of evidence currently to support optimal moisturiser choice. The ideal moisturiser should be conducive to scar maturation. Abstract: Scar management is a recognised key component of rehabilitation following burn. Moisturising often combined with massage is commenced once healing tissue has gained sufficient strength to tolerate surface friction, with the aim being to hydrate the dry scar. The studies on various moisturisers and creams provide some guidance on moisturiser selection, but many are inconclusive. Objective: This survey aimed to determine the current expert opinion regarding moisturiser recommendations, including the basis for these recommendations, across the burns community. Methods: A brief web-based survey was distributed to burn therapists via mailing lists of the Australian and New Zealand Burn Association (ANZBA), and American Burn Association (ABA) 'Occupational and Physical Therapist Burn Special Interest Group'. Results: The fifty three respondents indicated that there were 29 different moisturisers commonly recommended in practice. Three main themes were indicated as influencing recommendations for moisturiser: the perceived effects on the scar/skin (48%); the general properties of the moisturiser (38%); the ingredients (14%). Therapists reported that the principle stimuli determining their recommendations were patient feedback and the choice of the previous burn therapist in their service. Many were also guided by medical staff, pharmacists and sales representatives. Only three respondents were able to provide citations for published evidence supporting their recommendations. Conclusions: There is a paucity of evidence currently to support optimal moisturiser choice. This survey demonstrates that conflicting opinions are held on the ideal moisturiser brand, properties and ingredients. The recommendations made are based on low level evidence. Further research is required to inform clinicians which moisturiser to recommend to their clients. An ideal moisturiser should be one that is conducive to scar maturation, non- or minimally irritant, prevent skin drying, minimise transepidermal water loss and have no negative effect on barrier function.